The Effect of Cirata PV Power Plant Integration on Small-Signal Stability in the 500 kV Jawa-Bali System - NABILLYA ARGA NORMALITA; AWAN UJI KRISMANTO; IRRINE BUDI SULISTIAWATI (Institut Teknologi Nasional, Bandung, 2026)
Renewable energy resources (RES) integration significantly affects power system stability, corresponding with the system to maintain stable conditions when the system is subjected with small disturbance. In this research, the effects of Cirata integration on the Jawa Bali 500kV power system network's dynamic and small signal stability are analyzed. The critical eigenvalue trajectories showed that increasing power injection from PLTS improved the stability, it is indicated by the movement of critical eigenvalues to the left away from the imaginary axis, from σ = -1.253 to σ = -1.255. And is followed by an increase in the system damping ratio from 10,85% to 10,88%. These results indicate that the integration provides a positive contribution to damping oscillations and increasing system stability when faced with small disturbances.